(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Summary: Moringa oleifera is an edible plant that has been reputed to be a miracle plant by numerous authors, with effects on practically every body system. Phytochemical analyses have demonstrated that the leaves are rich in various minerals, vitamins and antioxidants. Its use in some continents dates back to Antiquity. Neurodegeneration are chronic diseases of the nervous system. There is currently an increase in the use of natural products to combat these debilitating diseases. So far, no suitable cure has been found, and conditions are managed and the symptoms treated. This article reviews the literature on the effects of Moringa oleifera leaves on the nervous system in vivo and in vitro.